Menanamkan Nilai Anti Korupsi Sejak Dini: Sosialisasi DI SMPN7 Tambang Pekanbaru - Emi vitaliani; Nur Azizah; Yovanna Nabila Azzahra; Ilham Hudi (STIKes Ibnu Sina Ajibarang, 2024)
The aim of this service is to strengthen understanding of anti-corruption values ​​and prevent unethical and corrupt behavior among students, especially in the school environment. The service method used in this activity is in the form of socialization which includes distributing posters, providing material followed by a question and answer session. , with special emphasis on instilling anti-corruption values ​​in today's young generation from an early age. When compared between pre-test and post-test activities, there is a very large difference in percentages before and after receiving the material. In the pre-test, 20 students answered 30% from 10 questions correctly and 70% incorrectly. In contrast, in the post-test, the same students answered 95% of the 10 questions correctly and 5% incorrectly. It can be concluded that through socialization, providing educational materials and discussions, participants were able to understand the teaching of values. anti-corruption values ​​from an early age. The findings of this service highlight the importance of instilling anti-corruption values ​​in students from an early age in everyday life.